Multi-day delay to care identified in pediatric trauma cases during COVID-19. Issue 1 (17th August 2021) - Shaw, Kylie G.; Salton, Reba L.; Carry, Patrick; Hadley-Miller, Nancy; Georgopoulos, Gaia
Abstract : This study aims to establish how pediatric fracture patterns were altered at a level 1 trauma center in a state that implemented a shutdown during the initial height of COVID-19. After IRB approval, we identified 2017 patients treated at a pediatric institution for definitive management of a fracture between 26 March and 31 May 2018, 2019, or 2020. Dates were chosen based on statewide stay-at-home orders for Colorado. Patients were excluded for treatment at another institution ( n = 148), no fracture noted in clinic ( n = 18), or other ( n = 13). Data were retrospectively collected from the remaining 1838 patients regarding demographics, fracture injury, mechanism, and treatment. Odds ratios (ORs) were calculated for each variable during COVID-19 relative to prior years. The number of fractures during 2020 decreased by 26% relative to 2019 and 23% to 2018. A larger proportion of patients experienced at least a 5-day delay to definitive treatment [OR: 1.55, confidence interval (CI): 1.23–1.96, P = 0.0002]. Rates of non-accidental trauma (NAT) increased non-significantly (OR: 2.67, CI: 0.86–8.32, P = 0.0900) during 2020 (1.2%) relative to 2018 (0.6%) and 2019 (0.3%). Fractures occurring at home increased to 79.9% (OR: 6.44, CI: 5.04–8.22, P < 0.0001). Despite less overall trauma during shelter-in-place orders, greater fracture numbers were seen among younger children and severe fractures were likely among older children. Patients may hesitate to seek care during 2020. Rates of NAT doubled during 2020. As communities prepare for future waves, treatment centers should warn against common fracture mechanisms and raise awareness of NAT.